If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7v + 3(v + -2) = -18 Reorder the terms: -7v + 3(-2 + v) = -18 -7v + (-2 * 3 + v * 3) = -18 -7v + (-6 + 3v) = -18 Reorder the terms: -6 + -7v + 3v = -18 Combine like terms: -7v + 3v = -4v -6 + -4v = -18 Solving -6 + -4v = -18 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -4v = -18 + 6 Combine like terms: -6 + 6 = 0 0 + -4v = -18 + 6 -4v = -18 + 6 Combine like terms: -18 + 6 = -12 -4v = -12 Divide each side by '-4'. v = 3 Simplifying v = 3
| 5x+8=-25+2x | | 66-4x=5x+19 | | 21-3f=9 | | 11-10x=56-31x | | 3X-4=10X-42 | | 5x+208=13x-8 | | 5-10x=45-38x | | 3x-30=15 | | -3x+1=-47+3x | | 3x+72=87 | | (x*x)+160x=6000 | | 7x-2=-2x | | x-9+4x=-54 | | -4x+5y+z=15 | | 3x+31=6x-5 | | 8-10x=24-17x | | 7x+3+6x=-153 | | 15x-2x^2-x^3=0 | | x+3+x=1 | | x^2-15x+6=0 | | 2y^2=5y+3 | | x^2+2-3=0 | | 8x+40=6x-70 | | 3-x+6x=-17 | | 2+n=5n-4 | | 0.75x^2-2x+4=0 | | x=2-0.8x | | 126-7x=11x+20 | | 2x^3+16x+18x^2=0 | | (x+3)/2=(x-3)/5 | | -3*-3-3-c=0 | | (x-2)/3=(x+1)/4 |